Price and income as determinants of the demand for luxury goods in Brazil: an econometric study with imports from the Mercosur Common Nomenclature - Scalco, Paulo Roberto; Lippi, Mariana Klaold; Almeida, Marcos Inácio Severo de (Revista de Administração da UFSM, 2015)
This article offers an alternative approach as promote an analysis on the determinants of demand for luxury products with data of more than a thousand imported products of the table of Mercosur Common Nomenclature (NCM). Through the volume of imports between January 2000 and March 2011 two hypotheses were tested about the determinants of demand: price and income. The results show that only income is statistically significant in determining the demand. These results are in agreement with what is discussed in economic theory, which defines luxury goods as those whose income elasticity of demand is greater than one. The non-statistical significance of the price factor may be result of a methodological limitation due to the use of the proxy for price or may be the result of non-functional characteristics of demand: consumers of luxury purchase them even in the face of higher prices.